2015
DOI: 10.1002/jobm.201500487
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of a novel bioemulsifier in crude oil degradation by Acinetobacter beijerinckii ZRS

Abstract: Bioemulsifiers can be applicated in a variety of areas such as bioremediation and microbial-enhanced oil recovery. The present study was aimed at bioemulsifier production, optimization, stability studies, and applications of the bioemulsifier produced by one of these strains, Acinetobacter beijerinckii ZRS. When Acinetobacter beijerinckii ZRS is cultured with hexadecane as a carbon source, it produces a novel extracellular emulsifying agent that does not cause remarkable reductions in surface tension. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
(59 reference statements)
0
11
0
10
Order By: Relevance
“…Maximum emulsification activity noted for Acinetobacter junii SC14 is 1759.8 EU ml −1 followed by A. calcoaceticus BD4, i.e., 593 EU ml −1 . Emulsification activity in % is also recorded for some BE and it was found that A. calcoaceticus RAG‐l showed maximum activity, i.e., 80.75% followed by two other strains such as A. calcoaceticus MM5 and A. beijerinckii ZRS, i.e., 80% . Most of the BE showed applications in degradation of variety of oils and aromatic as well as aliphatic hydrocarbons.…”
Section: Bioemulsifiers (Be) and Biosurfactants (Bs) Produced By Acinmentioning
confidence: 90%
See 4 more Smart Citations
“…Maximum emulsification activity noted for Acinetobacter junii SC14 is 1759.8 EU ml −1 followed by A. calcoaceticus BD4, i.e., 593 EU ml −1 . Emulsification activity in % is also recorded for some BE and it was found that A. calcoaceticus RAG‐l showed maximum activity, i.e., 80.75% followed by two other strains such as A. calcoaceticus MM5 and A. beijerinckii ZRS, i.e., 80% . Most of the BE showed applications in degradation of variety of oils and aromatic as well as aliphatic hydrocarbons.…”
Section: Bioemulsifiers (Be) and Biosurfactants (Bs) Produced By Acinmentioning
confidence: 90%
“…All carbon sources used by different strains of Acinetobacter showed influence on bioemulsifier production and helped in increasing yield of the same. Among all BE, maximum yield recorded is 5.16 g L −1 for lipoprotein bioemulsifier produced by A. beijerinckii ZRS, followed by lipoglycan nature of bioemulsifier (5.05 g L −1 ) produced by Acinetobacter baumanii AC5 . Hayder, reported use of 1% olive oil and sesame oil (edible oil) in production media increased yield of bioemulsifier to the maximum extent .…”
Section: Bioemulsifiers (Be) and Biosurfactants (Bs) Produced By Acinmentioning
confidence: 95%
See 3 more Smart Citations